Sustainable development goals: legally realistic or overambitious towards the development of the nations? - Saidatul Nadia Abd Aziz,; Salawati Mat Basir, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Sustainable Development Goals (SDGs) are the United Nations’ latest strategy to fight the issues of health, environment, and society that are currently afflicting the world. Though the 17 SDGs are highly anticipated to be the key in achieving the global development, the goals which equipped with 169 targets are said to be fairy tales, dressed in the bureaucratese of intergovernmental narcissism, decorated with robes of multilateral paralysis, and poisoned by the acid of nation-state failure. The MDGs were criticized for being too simple and narrow focused, but conversely the SDGs have been criticized for being too complex to realistically achieve. The main problem with the SDGs seems to be related with having a set of goals that are desirable yet too ambitious to achieve in reality. Therefore, the first part of this paper will discuss on the emergence of SDGs from their predecessor-MDGs, and the aftermath of MDGs. Part 2 of the paper will then discuss on the legal challenges of the implementation of SDGs which includes the lack of clarity and imprecise definitions of each goals, difficulty to translate the goals into actionable development outcomes, as well as the problem in strengthening governance. Since the goal needs to make measurable and actionable to realise the sustainable development by 2030, the author will then provide recommendations in Part 3, which will constitute to a cohesive framework that will be relevant to make the SDGs reliable goals for the development of the nations. The research finds that the SDGs are over ambitious and impossible to achieve the targets by 2030. However, the initiative to help in achieving global development must not be wasted, therefore powerful and realistic measures are obviously a necessity to make SDGs a success.